2018
DOI: 10.5755/j01.itc.47.2.16277
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion Detection in Cyber-Physical Systems Based on Petri Net

Abstract: Intrusion detection is a major concern in Cyber-Physical Systems (CPSs). In this paper, an algorithm based on Petri Net (PN) is proposed that simultaneously detects misuse and anomaly behavior of the system. The proposed anomaly detection method is applicable to Supervisory Control and Data Acquisition (SCADA) system at the highest level of CPSs. Neural First Order Hybrid Petri Net model (NFOHPN) with online fast Independent Component Analysis (ICA) is proposed for anomaly detection. It is shown that the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Specification-based techniques are applied for specific protocols, standalone or in combination with other methods [45], [46], [51]. More comprehensive solutions use a number of integrated techniques to detect a variety of attacks more accurately [43], [46], [48], [52], [53], [61].…”
Section: A Detection Methodology Protected Protocols and Implementamentioning
confidence: 99%
See 1 more Smart Citation
“…Specification-based techniques are applied for specific protocols, standalone or in combination with other methods [45], [46], [51]. More comprehensive solutions use a number of integrated techniques to detect a variety of attacks more accurately [43], [46], [48], [52], [53], [61].…”
Section: A Detection Methodology Protected Protocols and Implementamentioning
confidence: 99%
“…Ghazi and Doustmohammadi describe an algorithm based on Petri Net that simultaneously detects misuse and anomaly behavior of the cyber physical system [53]. Anomaly detection is based on Neural First Order Hybrid Petri Net (NFOHPN) with online fast independent component analysis (multivariate statistical method).…”
Section: F Hybrid Techniquesmentioning
confidence: 99%
“…Werlinger et al [14] state that the result of using IDS is not always clear. It is also interesting that practically the same imperfections have existed for many years [3], [15], [16] and even the new methods [13] [17] do not help to avoid them.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Heo et al [23] suggested a system design that helps to maintain a certain level of quality of service and quality of security service in threatening environments. Nevertheless, despite all the advantages provided by such systems, they still have many deficiencies that are fully disclosed in the papers [16][17][18][19][20][21].…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Intrusion detection [14] was proposed in CPS based on the Petri Net (PN). The main aim of this technique was simultaneously detecting misuse and anomaly characteristics of the CPSs.…”
Section: Survey On Cyber-attack Detection Schemesmentioning
confidence: 99%